Quality of life and body image after bariatric and body contouring surgery - Cristina Machado Bragança Moraes; Giancarlo Cervo Rechia; Glauco da Costa Alvarez; Clandio Timm Marques; Deise Silva de Moura; Raquel Pippi Antoniazzi (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: The demand for body contouring surgery after bariatric surgery is largely due to dissatisfaction with body image impaired by sagging and excess skin resulting from massive weight loss. This study aimed to evaluate the quality of life and body image of patients undergoing bariatric surgery and body contouring surgery in a private clinic. Method: This cross-sectional study compared 4 groups of 21 patients, matched by body mass index and age before undergoing bariatric surgery. They were divided into times before/after bariatric surgery and before/after body contouring surgery, thus forming groups A, B, C, and D, respectively. The SF-36 questionnaire assessed the quality of life, and the Silhouette Scale proposed by Kakeshita to assess body image. For the significance level, p<0.05 was chosen. Results: There was an improvement in all SF-36 domains after bariatric surgery. Patients who sought body contouring surgery had the lowest mental health component value, with little change after body contouring surgery. Almost all groups overestimated their silhouette, except for the group of 6 months after bariatric surgery, which saw itself as smaller. Conclusion: Bariatric patients seeking body contouring surgery have lower mental health-related quality of life scores that remain lower after body contouring surgery.